The Influence Of Financial Technology For Bank Syariah In Indonesia - Immawan Muhajir Kadim; Ferri Alfadri; Bazyad Abdullah Meteab Mubarak; Nurul Widad binti Abu Hassan (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
Based on data during the Covid-19 pandemic, the use of fintech lending experienced a spike from 62 companies to 162 companies and then decreased again after the Covid-19 pandemic to 129 companies and fell again to 102 companies in 2022. The aim of this research is to find out What is the influence of financial technology on Indonesian sharia banks in 2018-2022. This research uses a qualitative method. The data source used is secondary data obtained from the official OJK website. The data processing and data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The results of this research are the influence of financial technology on Indonesian sharia banks from 2018-2022. It can be seen that the use of fintech makes transactions at Indonesian sharia banks increase. This can be seen in 2018, namely 41.9 million transactions. Then in 2019 BRI Syariah Bank had many improvements with the use and development of financial technology as a strategy to attract customers. In 2020, during the Covid-19 pandemic, financial technology played a vital role in maintaining bank health. In 2021, even though Indonesian sharia banks are only 1 year old and under social restrictions by the government due to Covid 19, Indonesian sharia banks can still survive and provide services to customers through bank digitalization. In 2022 the sharia banking industry will also record positive growth. Total assets in December 2022 will increase by IDR. 108 trillion or grew 15.6% (yoy), to IDR 802.3